Constitutional Reconstruction of Legislative Authority Toward Strong Bicameralism in the Indonesian State System - Sheehan Ghazwa Mahardhika; Tunggul Anshari Setia Negara; Ngesti Dwi Prasetyo (IJBLE Scientific Publications Community Inc., 2026)
This article examines the constitutional politics of Indonesia's post-amendment bicameral legislature, with particular attention to the asymmetric distribution of legislative authority between the People's Representative Council (Dewan Perwakilan Rakyat, DPR) and the Regional Representative Council (Dewan Perwakilan Daerah, DPD). Although the 1999-2002 constitutional amendments formally introduced the DPD as a territorial chamber, Articles 20 and 22D of the 1945 Constitution leave the DPR with decisive legislative authority while the DPD remains limited to initiating selected bills, participating in restricted deliberations, and issuing non-binding considerations. Using normative-juridical legal research supported by statutory, historical, conceptual, and comparative constitutional approaches, this article argues that Indonesia's bicameralism is not merely imperfect but structurally weak because regional representation is institutionally present yet legally unable to determine legislative outcomes. Drawing on Sartori's, Lijphart's, and Tsebelis and Money's bicameral theory, Pitkin's theory of substantive representation, Habermas's deliberative democracy, and constitutional theories of limited government, the article proposes the National Plenary Legislative Model as a constitutional reconstruction toward strong bicameralism. The model reconstitutes the People's Consultative Assembly (Majelis Permusyawaratan Rakyat, MPR) as a national deliberative plenary forum in which the DPR acts as the political chamber and the DPD as a territorial chamber with co-decisional authority in matters affecting regional autonomy, intergovernmental fiscal relations, natural resources, and regional formation. The proposed reconstruction preserves Indonesia's unitary state while strengthening intra-legislative checks and balances, substantive regional representation, and Pancasila-based deliberative constitutionalism.